Wephouria Fest 2026 di Tanah Grogot sebagai Bisnis Bazaar-Cultural Event - Ibnu Khayath Farisanu; Wahyudi Wahyudi; Syifi Fauziah; Dedy Darmawan; Indri Farradina; Rusmiati Rusmiati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The paradigm shift in higher education requires universities to act as nodes for regional economic growth through experiential learning models. This community service (PkM) program aims to reconstruct a youth cultural event into an institutionally designed bazaar-cultural event to accelerate the capacity of student startup entrepreneurs. The program was integrated into the Wephouria Fest 2026 at STIE Widya Praja Tanah Grogot, Paser Regency, involving alliance consisting of academic institutions, student bodies, alumni, and cross-sector corporate sponsors. The method applied combined community education, interactive mentoring, and institutional space policy facilitation through three phases: situation analysis, clinical on-site mentoring, and mixed-methods outcome evaluation. The results indicated that the program successfully transformed the campus courtyard into a functional